Extent of Utilization of Different ICT Tools by the Teachers of Agricultural Universities - Kumar, Vikas; Khan, I.M.; Sisodia, S.S. (Indian Journal of Extension Education, 2019)
Information and communication technology (ICT) in education is the method of education that use information and communication technology to support, improve, and optimize the delivery of information. The study was conducted in three purposively selected agricultural universities in Rajasthan total nine constituent colleges were selected from these three agricultural universities. For the study purpose. 60 per cent of teachers were selected from every college by using simple Random sampling technique. In all the selected agricultural universities combinedly 59.04 per cent teachers were having medium utilization of selected ICT tools. Among the different ICT tools the agricultural university teachers were having highest utilization of internet (MPS 96.73) followed by e-mail (MPS 96.20). There was no significant difference between the teachers of SKNAU, Jobner, SKRAU, Bikaner and MPUAT, Udaipur with regard to their utilization of different ICT tools.
Keywords: Agricultural universities; ICT tools; Utilization; Teachers